MACROECONOMIC BALANCE AND NEUTRAL MONETARY POLICY - V. K. Krylov (Вестник университета)
The problem of macroeconomic equilibrium as a theoretical basis for monetary policy has been considered. In this regard, the concept of long-term equilibrium and money neutrality has been criticized. The position on the non-equilibrium nature of economic development has been supported. As a result, it has been concluded that it is impossible to switch to a neutral monetary policy, and therefore to establish a neutral key rate. The interest theory of K. Wicksell, his concepts of monetary and natural interest rates has been characterized. The futility of attempts to quantify the neutral interest rate has been shown. It has been concluded that the absence of radical changes in monetary policy carries with it the risk of permanent economic stagnation.